2013
DOI: 10.1074/jbc.m112.427047
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of γ-Aminobutyric Acid (GABA) Metabolism and Function in the Social Amoeba Dictyostelium discoideum

Abstract: Background: GABA promotes terminal differentiation during late development of Dictyostelium discoideum. Results: GABA metabolism is tightly controlled and regulates early development. Conclusion: Distinct genes regulate GABA signaling during different developmental stages. Significance: This is the first systematic study of GABA metabolism in Dictyostelium discoideum and broadens our knowledge of the evolution and function of GABA metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…4 D). Dictyostelium has a GABA signalling system, which is active during development ( Taniura et al, 2006 ; Anjard and Loomis, 2006 ; Wu and Janetopoulos, 2013 ) and we found that GABA and L-glutamate both evoke a cytoplasmic calcium signal from aggregation-competent cells, although this was erratic ( Fig. 4 B,C).…”
Section: Resultsmentioning
confidence: 69%
“…4 D). Dictyostelium has a GABA signalling system, which is active during development ( Taniura et al, 2006 ; Anjard and Loomis, 2006 ; Wu and Janetopoulos, 2013 ) and we found that GABA and L-glutamate both evoke a cytoplasmic calcium signal from aggregation-competent cells, although this was erratic ( Fig. 4 B,C).…”
Section: Resultsmentioning
confidence: 69%
“…discoideum genome encodes 14 class C GPCRs, including fAR1, that contain extracellular VFT domains. Bioinformatics analysis suggested that the VFT domain of these members are evolutionarily closer to bacterial PBPs and eukaryotic GABA B Rs family than to other class C GPCRs [ 47 , 48 ], constituting the prototype of class C GPCRs with a variety of physiological functions [ 49 ]. Interestingly, bacterial PBPs bind various ligands, while most mammalian class C GPCRs expressed in the central nerve system bind only one natural ligand, implying that during evolution, VFT domains of class C GPCRs underwent partial loss of function, such as the ability to bind various ligands [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, inclusion body hepatitis can reduce the level of Bu‐Ia + B lymphocyte in chicken (Wang and Wang, ), implying that the decline of Bu‐Ia + B lymphocytes under HS may be related to inflammatory response. The promotion of B lymphocyte development by GABA under HS is possibly achieved by enhancing the metabolism and providing a large amount of energy substances such as glutamate (Akcay et al., ; Wu and Janetopoulos, ).…”
Section: Discussionmentioning
confidence: 99%